2023
DOI: 10.1186/s13046-022-02591-z
|View full text |Cite
|
Sign up to set email alerts
|

“Proteotranscriptomic analysis of advanced colorectal cancer patient derived organoids for drug sensitivity prediction”

Abstract: Background Patient-derived organoids (PDOs) from advanced colorectal cancer (CRC) patients could be a key platform to predict drug response and discover new biomarkers. We aimed to integrate PDO drug response with multi-omics characterization beyond genomics. Methods We generated 29 PDO lines from 22 advanced CRC patients and provided a morphologic, genomic, and transcriptomic characterization. We performed drug sensitivity assays with a panel of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Overall, our data indicate that PDO models are able to reproduce the results observed in the patient, as also previously reported by Papaccio et al . [ 39 ], demonstrating the technical feasibility of performing HIPEC treatments with PDOs in a clinically relevant setting.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data indicate that PDO models are able to reproduce the results observed in the patient, as also previously reported by Papaccio et al . [ 39 ], demonstrating the technical feasibility of performing HIPEC treatments with PDOs in a clinically relevant setting.…”
Section: Discussionmentioning
confidence: 99%
“…37 The abundance of intra-tumor stromal cells and the inter-epithelial cancer cell heterogeneity causes challenges in the genetic sequencing of PC. 38 However, in comparison with the primary tumors, organoids that only comprise epithelial cells offer amplified signals, enabling the comprehensive sequencing of tumor cells and identification of mutations. Understanding PDO cellular state heterogeneity is pivotal for elucidating their potential as personalized models.…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…24 Tumoroids retain parental tumor heterogeneity and histopathological features and reserve their 3D structure after long-term culture 32,33,[205][206][207] (Table 1). Papaccio et al 208 reported that patient-derived colorectal tumoroids represented the morphology and immunohistochemistry characteristics and genomic and transcriptomic profile of corresponding tissues, and the response to anticancer drugs varied among these tumoroids derived from different patients. The role of mutations in genes or structures in tumor development is difficult to observe dynamically or to intervene.…”
Section: Cancersmentioning
confidence: 99%
“…Papaccio et al. 208 reported that patient‐derived colorectal tumoroids represented the morphology and immunohistochemistry characteristics and genomic and transcriptomic profile of corresponding tissues, and the response to anticancer drugs varied among these tumoroids derived from different patients.…”
Section: Biomedical Applications Of Organoidsmentioning
confidence: 99%